Ibu Rumah Tangga: Streotype Perempuan Pengangguran - Heri Junaidi (Pusat Studi Gender dan Anak Universitas Islam Negeri Raden fatah palembang, 2017)
The building of the household Division the role of structure members. In many ways, the role of women truly are always in the most important constellations in domestic life. Study of Denys Lombard and Geertz among studies that give the conclusion. Along with this, the reality is still a demonstration of counterproductive, as the phrase is still socialized